Intra-strain phenotypic and genomic variability of the commercial Saccharomyces cerevisiae strains Zymaflore VL1 recovered from vineyard environments - Duarte, Ricardo Franco (2012)
The use of commercial Saccharomyces cerevisiae wine strains as fermentation starters has been extensively generalised over the past two decades. These strains are used by wineries every harvest in large quantities. We showed that such strains are disseminated from the winery and their permanence in nature induced genetic changes, not found among a control group of isolates that derived from clonal expansion of the commercial “mother” strain. The objective of the present study was to evaluate by comparative genome hybridization on array (aCGH) the genome variations among four isolates of the commercial strain S. cerevisiae Zymaflore VL1, re-isolated from vineyards surrounding the wineries where this strain was applied, in comparison to the commercial “mother” strain. Data analysis showed genetic differences among the recovered isolates in comparison with the “mother” strain. Amplification (1 to 2 fold changes) of 14 genes were detected, related with mitosis (SHE1), meiosis (HFM1), lysine biosynthesis (LYS14), galactose (GAL1) and asparagine catabolism (ASP3-2). ASP3-2 amplification is in agreement with the previously shown increased expression during nitrogen starvation. This might occur as adaptation to natural environments with poor yeast-utilizable nitrogen sources. Eight Ty elements were also amplified, whereas each of the recovered strains had a unique amplification pattern. SNP analysis of the four isolates strengthened the hypothesis of microevolutionary changes, as complement to the aCGH approaches. A phenotypic screening was performed considering 28 physiological tests. Seven phenotypic traits distinguished the recovered strains from the “mother” strain which was unable to grow at 18ºC, but evidenced some growth in the presence of CuSO4(5mM) and SDS 0.01%(v/v). Variable growth patterns were found for NaCl(1.5M), KHSO3(300mg/L) and wine supplemented with glucose (0.5% and 1%w/v). Sequencing and genome comparison of the five isolates is currently underway. We hypothesize that the transition from nutrient-rich musts to nutritionally scarce natural environments induces adaptive responses and microevolutionary changes promoted by Ty elements. These changes (and possibly others as well) may contribute to intra-strain phenotypic variability.